The Ashmolean Museum crossing cultures, crossing time - Wodehouse, Katherine (Ashmolean Museum, 2014)
"The Ashmolean opened its doors on 21 May 1683, making it Britain's first public museum. It now ranks as one of the world's great collections of art and archaeology with an extraordinary range of objects from prehistory to the present day spanning Antiquities, Western and Eastern Art, Coins and Casts. This is the most comprehensive introduction ever published to the riches of the Ashmolean. Over 400 key objects are discussed and illustrated, while an accompanying essay explores the Museum's fascinating history." -- Backcover